Analisis Kandungan Kadmium (Cd) pada Sedimen di Perairan Teluk Totok, Minahasa Tenggara (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Heavy metal contamination in coastal waters is an environmental issue that affects ecosystem balance and public health. Cadmium (Cd) is a non-essential heavy metal that is toxic, persistent, and has the potential to accumulate in aquatic sediments. This study aimed to analyze cadmium (Cd) concentrations in sediments from Totok Bay and compare the results with the applicable sediment quality standards. A quantitative descriptive design was employed using field surveys and laboratory analyses. Sediment samples were collected from 16 sampling points using a purposive sampling method at a depth of 10–15 cm. Cadmium concentrations were analyzed using the Inductively Coupled Plasma (ICP) method at the Makassar Public Health Laboratory. The results showed that cadmium concentrations in all 16 sediment samples were below the instrument detection limit (